Exploring the Predictive Role of Early Executive Functions and Self-Regulation on Functional Outcome in Neurodevelopmental Disorders: A Systematic Review and Meta-analysis - Berni M.; Scatigna S.; Igliozzi R.; Mazzotti S.; Calderoni S.; Martinelli A.; Tancredi R.; Guzzetta A.; Pecini C. (Neuropsychology Review, 2025)

Haptic and visuo-haptic impairments for object recognition in children with autism spectrum disorder: focus on the sensory and multisensory processing dysfunctions - G. Purpura; S. Petri; R. Tancredi; F. Tinelli; S. Calderoni (Experimental Brain Research, 2024)
Dysfunctions in sensory processing are widely described in individuals with autism spectrum disorder (ASD), although little is known about the developmental course and the impact of these difficulties on the learning processes during the preschool and school ages of ASD children. Specifically, as regards the interplay between visual and haptic information in ASD during developmental age, knowledge is very scarce and controversial. In this study, we investigated unimodal (visual and haptic) and cross-modal (visuo-haptic) processing skills aimed at object recognition through a behavioural paradigm already used in children with typical development (TD), with cerebral palsy and with peripheral visual impairments. Thirty-five children with ASD (age range: 5–11 years) and thirty-five age-matched and gender-matched typically developing peers were recruited. The procedure required participants to perform an object-recognition task relying on only the visual modality (black-and-white photographs), only the haptic modality (manipulation of real objects) and visuo-haptic transfer of these two types of information. Results are consistent with the idea that visuo-haptic transfer may be significantly worse in ASD children than in TD peers, leading to significant impairment in multisensory interactions for object recognition facilitation. Furthermore, ASD children tended to show a specific deficit in haptic information processing, while a similar trend of maturation of visual modality between the two groups is reported. This study adds to the current literature by suggesting that ASD differences in multisensory processes also regard visuo-haptic abilities necessary to identify and recognise objects of daily life.